Efficacy and safety of saxagliptin in patients with type 2 diabetes: A systematic review and meta-analysis. - Peng Men; Xiao-Tong Li; Hui-Lin Tang; Suo-di Zhai (PLoS ONE)
Objective To evaluate the comparative efficacy and safety of saxagliptin for type 2 diabetes (T2D). Methods A systematic search of PubMed, Embase, the Cochrane Library, Web of Science, ClinicalTrials.gov and two Chinese databases for randomized controlled trials (RCTs) comparing saxagliptin with placebo or active comparators was performed up to July 2017. A complementary search was done to cover literature until March 2018. For continuous data, estimates were pooled using inverse variance methodology to calculate weighted mean differences (WMDs). Dichotomous data were presented as Mantel-Haenzel risk ratios (RRs). Results Thirty-nine references of 30 RCTs involving 29,938 patients were analyzed. Compared with placebo, saxagliptin significantly reduced glycated hemoglobin (HbA1c, WMD -0.52%, 95% CI -0.60 to -0.44) and fasting plasma glucose (WMD -13.78 mg/dL, 95% CI -15.31 to -12.25), and increased the proportion of patients achieving HbA1c <7% (RR 1.64, 95% CI 1.53 to 1.75). When combined with submaximal-dose metformin, saxagliptin significantly increased the proportion of patients achieving HbA1c <7% compared with acarbose (RR 2.38, 95% CI 1.17 to 4.83) and uptitrated metformin (RR 1.30, 95% CI 1.04 to 1.63). Saxagliptin was similar to other DPP-4 inhibitors but inferior to liraglutide and dapagliflozin on glycemic control. Saxagliptin significantly decreased the incidences of overall adverse events compared with acarbose (RR 0.71, 95% CI 0.57 to 0.89) and liraglutide (RR 0.41, 95% CI 0.24 to 0.71) when added to metformin. Weight gain and hypoglycemia with saxagliptin was slightly but significantly higher than placebo and lower than sulfonylureas. Saxagliptin did not increase the risk of arthralgia, heart failure, pancreatitis and other adverse events. Conclusions Generally, saxagliptin has similar efficacy compared with most oral antidiabetic drugs and may be more effective than acarbose, while having a better safety profile than both acarbose and sulfonylureas.